Engineering multi-agent systems using feedback loops and holarchies. (October 2016) - Basso, Gillian; Cossentino, Massimo; Hilaire, Vincent; Lauri, Fabrice; Rodriguez, Sebastian; Seidita, Valeria
Abstract: This paper presents a methodological approach for the engineering of Multi-Agent Systems using feedback loops as a first class concept in order to identify organizations. Feedback loops are a way for modeling complex systems that expose emergent behavior by means of a cause-effect loop between two levels called micro and macro levels of the system. The proposed approach principles consist in defining an abstract feedback loop pattern and providing activities and guidelines in order to identify and refine possible candidates for feedback loops during the analysis phase of the Aspecs methodology. This approach is illustrated by using an example drawn from the smart grid field.